Analysis of Car-to-Car Beaconing with Network Coding - Ali, Nasir; Baselt, Daniel; de Meer, Hermann (Electronic Communications of the EASST, 2011)
Lack of updated information due to a high beacon loss rate is a key challenge in car-to-car beaconing strategies. One potential solution for this issue is to re-broadcast lost beacons. However, the repeated dissemination of each lost beacon is infeasible due to the limited bandwidth of wireless channels. To overcome this limitation, network coding is a promising technique, through which a node combines (i.e. codes) multiple packets from different sources and re-broadcasts them through one transmission for the efficient bandwidth usage. In the past, network coding has been employed only for data packets. In this paper, this idea is used for periodic beacons in car-to-car communication to analyze, how much it is effective for the recovery of lost beacons. To this end, we propose two approaches: random selection and radius-based, and compare them to determine, which scheme recovers more beacons. We evaluate these approaches in both sparse and dense highway traffic scenarios with probabilistic radio propagation characteristics.